2016
DOI: 10.1177/1077801216654017
|View full text |Cite
|
Sign up to set email alerts
|

Sexist Humor and Rape Proclivity: The Moderating Role of Joke Teller Gender and Severity of Sexual Assault

Abstract: Three experiments examined the effect of sexist humor on men's self-reported rape proclivity (RP). Pilot study demonstrated that people differentiate the five rape scenarios of Bohner et al.'s. RP Scale based on the degree of physical violence perpetrated against the victim. Experiment 1 demonstrated that men higher in hostile sexism report greater RP upon exposure to sexist jokes when a woman (vs. a man) delivers them, and that this effect is limited to rape scenarios depicting a moderate versus a high level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
5
13
0
Order By: Relevance
“…In this regard, it has been established that sexist humor creates a norm of tolerance of sexual discrimination, which in turn leads to a higher tolerance of sexist events (Ford, 2000), the acceptance of societal sexism (Ford et al, 2013), and a greater willingness to discriminate against women (Ford et al, 2008). Most notably for the present research, men exposed to sexist humor have reported greater propensity to commit sexual violence against women, including rape (Romero-Sánchez et al, 2010, 2017), particularly when the male recipients of this type of humor exhibit sexist attitudes (e.g., Thomae & Viki, 2013).…”
mentioning
confidence: 58%
See 3 more Smart Citations
“…In this regard, it has been established that sexist humor creates a norm of tolerance of sexual discrimination, which in turn leads to a higher tolerance of sexist events (Ford, 2000), the acceptance of societal sexism (Ford et al, 2013), and a greater willingness to discriminate against women (Ford et al, 2008). Most notably for the present research, men exposed to sexist humor have reported greater propensity to commit sexual violence against women, including rape (Romero-Sánchez et al, 2010, 2017), particularly when the male recipients of this type of humor exhibit sexist attitudes (e.g., Thomae & Viki, 2013).…”
mentioning
confidence: 58%
“…Specifically, in situations in which prejudicial behavior is openly recriminated or in which non-tolerance to it is likely, prejudiced individuals will not express themselves freely but will instead let themselves be influenced by the social norm of “not being prejudiced.” However, disparagement humor in general, and sexist humor in particular, seem to act as a cue that makes it possible to express negative attitudes. Specifically, applying the prejudiced norm theory to the particular case of sexist humor, men who harbor hostile attitudes toward women are likely to see this type of humor as a way to freely express their prejudice without fear of social reprobation because it is “only a joke.” It must be noted at this point that disparagement humor against women in itself does not promote the acceptance and/or expression of prejudice communicated through humor in all men; instead, it is men with certain attitudes (i.e., hostile sexism) who are most influenced by this type of humor (e.g., Romero-Sánchez et al, 2010, 2017).…”
Section: Prejudiced Norm Theory: Sexist Humor and Violence Against Womenmentioning
confidence: 99%
See 2 more Smart Citations
“…These are typically seen as more acceptable than overt aggressive sexism or gendertrolling ( Mallett et al, 2016 ), and are sometimes used to defend sexist attitudes and behavior ( Fox et al, 2015 ). Although seemingly harmless, sexist humor is also detrimental in creating social norms that reinforce gender inequality, which may function as a trigger for increased acceptance of rape ( Romero-Sánchez et al, 2017 ; Thomae & Viki, 2013 ).…”
Section: Introductionmentioning
confidence: 99%